Plasminogen activator inhibitor-1 in acute hyperoxic mouse lung injury. - Barazzone, C (1996)
Hyperoxia-induced lung disease is associated with prominent intraalveolar fibrin deposition. Fibrin turnover is tightly regulated by the concerted action of proteases and antiproteases, and inhibition of plasmin-mediated proteolysis could account for fibrin accumulation in lung alveoli. We show here that lungs of mice exposed to hyperoxia overproduce plasminogen activator inhibitor-1 (PAI-1), and that PAI-1 upregulation impairs fibrinolytic activity in the alveolar compartment. To explore whether increased PAI-1 production is a causal or only a correlative event for impaired intraalveolar fibrinolysis and the development of hyaline membrane disease, we studied mice genetically deficient in PAI-1. We found that these mice fail to develop intraalveolar fibrin deposits in response to hyperoxia and that they are more resistant to the lethal effects of hyperoxic stress. These observations provide clear and novel evidence for the pathogenic contribution of PAI-1 in the development of hyaline membrane disease. They identify PAI-1 as a major deleterious mediator of hyperoxic lung injury.